1991
DOI: 10.1101/gad.5.3.475
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the guanine nucleotide-binding domains of a yeast G alpha protein confer a constitutive or uninducible state to the pheromone response pathway.

Abstract: Several domains of guanine nucleotide-binding proteins are conserved and form the guanine nucleotide-binding pocket. Mutations in these domains in EF-Tu, ras, and Gas have been shown to result in informative phenotypes. We made several analogous changes in SCG1, which encodes the ,x subunit of the G protein involved in pheromone response in yeast. The scgl L~sass and scgl An°a91 mutations resulted in s e v e r e growth and cell morphology defects; this phenotype is similar to the null phenotype and results fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 42 publications
2
51
0
1
Order By: Relevance
“…The pheromone response pathway is exquisitely sensitive to changes in Gpa1p expression (Cole et al, 1990;Kang et al, 1990). Studies of other GPA1 mutations have revealed different phenotypes when expressed on a centromere-based plasmid instead of the chromosomal locus (Miyajima et al, 1989;Kurjan et al, 1991). We found that haploid cells expressing the mutant allele as the sole copy of GPA1 were viable.…”
Section: Gpa1p Is Dually Myristoylatedmentioning
confidence: 78%
“…The pheromone response pathway is exquisitely sensitive to changes in Gpa1p expression (Cole et al, 1990;Kang et al, 1990). Studies of other GPA1 mutations have revealed different phenotypes when expressed on a centromere-based plasmid instead of the chromosomal locus (Miyajima et al, 1989;Kurjan et al, 1991). We found that haploid cells expressing the mutant allele as the sole copy of GPA1 were viable.…”
Section: Gpa1p Is Dually Myristoylatedmentioning
confidence: 78%
“…Other genetic observations suggested a direct interaction between SST2 and GPA1. First, certain mutations in the G␣ gene could bypass the requirement for a fully active SST2 gene (30,31). Second, the recovery-promoting effect of G␣ overexpression was more efficient if residual SST2 function was present (32,33).…”
Section: Establishing a Paradigm: Identification Of Yeast Sst2mentioning
confidence: 99%
“…We therefore tested the stability of the G␣ N388K mutant, whose phenotype is consistent with a defect in guaninenucleotide binding. G␣ N388K has been proposed to accumulate in the GTP-bound state, thereby preventing efficient interactions with G␤␥ (Kurjan et al 1991).…”
Section: An Activated Allele Of G␣ Exhibits Increased Susceptibility mentioning
confidence: 99%
“…G␣ s exhibits an accelerated rate of degradation after activation of the signalling pathway. Interestingly, a mutation in G␣ s (R201C) that slows the rate of GTP hydrolysis is associated with increased degradation (Kurjan et al 1991). Similarly, the yeast G␣ N388K mutant, which may be primarily bound to GTP, is rapidly degraded.…”
Section: Significance Of Regulated G␣ Stabilitymentioning
confidence: 99%
See 1 more Smart Citation